Hubungan Partisipasi Anak dalam Agro Educational Tourism dengan Minat pada Bidang Pertanian (Studi Kasus: Agrowisata Chelsea, Desa Taro, Kecamatan Tegallalang, Kabupaten Gianyar, Provinsi Bali) - DESAK GEDE MAYA AGREVINA; I GUSTI A.A LIES ANGGRENI; I MADE SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
The Relation of the Child’s Participation in Agro Educational Tourism to Their Interest in Agriculture (A Case Study: Chelsea Agrotourism, TaroVillage,Tegallalang District, Gianyar Regency. Bali Province) It seems that the young generation’s interest in agriculture has decreased in the lastseveral years. The decrease in the number of young people who work as farmers and thedecrease in the number of agricultural graduates show this. The Agro EducationalTourism is a combination of the agro-touristic activities and the concept of educationwhich is intended to promote agriculture widely. The Chelsea Agrotourism developed atTaro Village, Tegalallang District, Gianyar Regency, Bali Province shows the conceptof the education-based tourism. In this case, children are the target of tourists.Therefore, it was necessary to conduct research on the relationship of the children’sparticipation in agro educational tourism to their interest in agriculture. The children’sparticipation can inspire the young generation to choose agricultural education. Theresult of the study showed that the children involving in the outing activity offered bythe Chelse Agrotourism showed highly active participation. Their participation waspositively relevant to their interest. When their participation improves, their interest willbe better. It can be concluded, therefore, that it is good to promote the Agro Educational Tourism to improve the children’s interest in agriculture.